Internal Iliac Artery Stenosis: Diagnosis and How to Manage it in 2015 - Mahé, Guillaume; Kaladji, Adrien; Le Faucheur, Alexis; Jaquinandi, Vincent (Frontiers in Cardiovascular Medicine, 2015)
Lower extremity arterial disease (LEAD) is a highly prevalent disease affecting 202 million people worldwide. Internal iliac artery stenosis (IIAS) is one of the localization of LEAD. This diagnosis is often neglected when a patient has a proximal walking pain since most physicians evoke a pseudoclaudication. Surprisingly, IIAS management is reported neither in the Trans-Atlantic Inter-Society Consensus II nor in the report of the American College Foundation/American Heart Association guidelines. The aims of this review are to present the current knowledge about the disease, how should it be managed in 2015 and what are the future research trends.